Centella Asiatica sebagai Herbal untuk Kedokteran Preventif pada Bidang Mata,Telinga Hidung Tenggorokan, dan Psikiatri: Sebuah Sistematic Literature Review - Ardizal Rahman; Musda Hidayati; Donny Haryxon Tobing; Dwi Wijayanti (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Centella Asiatica, also known as gotu kola, is a widely used herbal plant in traditional medicine, especially across Asia. Recent studies have shown the preventive and therapeutic potential of Centella Asiatica in various medical conditions, particularly in eye health, otorhinolaryngology (ENT), and psychiatry. This systematic literature review aims to evaluate the scientific evidence regarding the preventive benefits of Centella Asiatica in these three health domains: ophthalmology, ENT, and psychiatry. Literature searches were conducted through PubMed, Google Scholar, Scopus, and ScienceDirect. Inclusion criteria included articles published in the last five years, studies using controlled clinical or experimental methods, and relevance to the use of Centella Asiatica in eye, ENT, and psychiatric health. The selection and evaluation process followed the PRISMA guidelines. A total of 12 studies met the inclusion criteria and showed positive findings on the preventive effects of Centella Asiatica in all three domains. Centella Asiatica demonstrates significant potential as a preventive agent in modern medicine, particularly for eye, ENT, and mental health issues. However, further research with stronger study designs and longer durations is needed to confirm these findings.